Unwind : UnDivided - Book 4 - Shusterman, Neal. (New York : Simon & Schuster Books for Young Readers, 2014)
Proactive Citizenry, the company that created Cam from the parts of unwound teens, has a plan: to mass produce rewound teens like Cam for military purposes. And the company has been suppressing technology that could make unwinding completely unnecessary. As Conner, Risa, and Lev uncover these startling secrets, enraged teens begin to march on Washington to demand justice and a better future. But Starkeys group of storked teens is growing more powerful and militant with each new recruit. And if they have their way, theyll burn the harvest camps to the ground and put every adult in them before a firing squad-- which could destroy any chance America has for a peaceful future.
870L
Accelerated Reader AR
Keywords: Fugitives from justice -- Fiction; Fugitives from justice; Juvenile fiction; Revolutionaries -- Fiction; Revolutionaries; Juvenile fiction; Fugitives from justice; Fiction; Revolutionaries; Fiction; Science fiction; Science fiction